O movimento dialético do valor: a dialética marxiana n’O capital - Miranda, Gutemberg da Silva (2020)
The movement of value is dialectical and is inserted in a value relationship. Use-value, as a transfer of value, occupies a central place in the value relation and represents the opposite of exchange value. The opposition between use-value and exchange value demonstrates the dialectical nature of value, and reveals it as a product of both social and historical relations. The value theory revealed in Capital emerged from Karl Marx's political economy critique and represents both a synthesis of Marxian philosophical reflections and the foundation from which Marx will develop his critique of capitalism. The purpose of this thesis work is to demonstrate the dialectical content inherent to the matter of value as Marx developed it in Capital. From a circular conception of value, we intend to demonstrate the dialectical movement of the Marxian categories as use-value, exchange value, value relation, body of value and value-form. Without dialectics, it is not possible to understand the concept of value as it moves within the Marxian analysis and is related to the dialectical categories of Capital. The body of value consists in the process of creating value between the opposite relative form and equivalent form of value, forms that are transformed into a value-form, sublating immediacy and the elements external to the value. Therefore, value is the effectiveness of the value-form, that is, the effectiveness of the value relation that is not to be confused with the expression of value or exchange value. The materiality of value consists in overcoming the dichotomy of the forms and also what is found external to the relation of value. When the expression of value ceases to represent an external element and becomes immanent to value, we can glimpse the dialectical emergence of the value-form. The material depository of value and the material content of value transform into a movement capable of overcoming the contradiction between relative form and equivalent form of value and find, in the value-form, the effectiveness of the dialectical movement of value itself. Hence, we can conclude that the value is the in itself and the for itself of the relation of value. The in itself and the for itself that manifest as value-form insofar as the dichotomy between use-value and exchange value is sublated through the substantial and dialectical unity of value.